Perhitungan Daya Roller Pada Alat Tangkap Bagan Tancap - Safingi Alamsyah; Berbudi Wibowo; Yaser Krisnafi (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
The Pangandaran lift net is a traditional fishing gear used by fishermen to catch small pelagic species such as anchovies and rebon shrimp. The traditional operation technique makes the lift net become less productive and highly dependent on the strength of the fishermen who operate it. The purpose of this study is to determine the amount of power needed to lift the net and catch when haulling on the lift net so that it can be used as a reference as a design tool for towing a roller. The analysis used is the analysis to determine the extent of the structure of fishing gear, catches, Drag force, Buoyancy and Gravity. The results showed that in the lift net which has dimensions of length, width and height measuring 10 x 10 x 15 meters and with a catch per setting of 200 kg, the roller of lift net must be able to lift a minimum load of 4488.4 newtons if the load is already above the surface of the water. However, catches and fishing gear that are lifted by roller charts with a speed of 0.05 meters / second produce a load of 327.2 newtons when in the water column with a density of 1025 kg / m3. Then the minimum power required by a roller chart is 22.44 kw.